2020
DOI: 10.1186/s12955-020-01582-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between health-related quality of life, acceptance of illness and characteristics of pregnant women with hyperglycemia

Abstract: Background The study was performed to evaluate the association between socio-demographic factors on the one hand, and quality of life and illness acceptance on the other, in pregnant women with hyperglycemia. Methods The study was performed in the years 2016–2017 in south-eastern Poland. The study included 676 women: 339 pregnant women with hyperglycemia in the case group, and 337 healthy pregnant women in the control group. The research instruments applied included the WHOQOL-BREF quality of life questionna… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 28 publications
(72 reference statements)
1
9
0
2
Order By: Relevance
“…Medium acceptance of illness was reported with lung cancer [ 26 ], type II diabetes mellitus [ 27 ], colorectal cancer [ 28 ], and breast cancer [ 29 ]. There are also studies which reported higher acceptance of illness among renal transplantation patients [ 30 ] and pregnant women with hyperglycemia [ 31 ]. Some studies also indicated a strong relationship between illness acceptance and quality of life [ 32 ], and the extent the patients accepts their chronic diseases has shown to impact their quality of life [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Medium acceptance of illness was reported with lung cancer [ 26 ], type II diabetes mellitus [ 27 ], colorectal cancer [ 28 ], and breast cancer [ 29 ]. There are also studies which reported higher acceptance of illness among renal transplantation patients [ 30 ] and pregnant women with hyperglycemia [ 31 ]. Some studies also indicated a strong relationship between illness acceptance and quality of life [ 32 ], and the extent the patients accepts their chronic diseases has shown to impact their quality of life [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…But only 9.4% (n = 9) had high acceptance of illness (scored[31][32][33][34][35][36][37][38][39][40]. The mean of overall acceptance of illness among epileptic patients was 21.04 with standard deviation of 7.21, which indicates medium level of acceptance of a disease among epileptic patients in the study area (Table2).…”
mentioning
confidence: 99%
“…Some studies have suggested that physical activity and mental health are positively associated with QoL[ 44 ]; it is well known that exercise enhances insulin signalling independent of PI3K and that glucose transport and GLUT4 translocation are enhanced as skeletal muscle contraction is stimulated by insulin[ 47 ]. Similarly, better education may lead to greater confidence, a sense of security, and building better relationships with others, contributing to mental health[ 48 ]. The mechanisms through which IR influences emotional regulation are being revealed by animal and human studies, and the brain requires glucose as an essential energy source[ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first two questions ask the opinion about the quality of life and general health. The remaining questions are grouped into four domains that are assessed separately: physical health (items 3,4,10,15,16,17,18), psychological health (5,6,7,11,19,26), social relationship (items 20,21,22), and environmental relationship (items 8,9,12,13,14,23,24,25). Each item has Likert-type response options, from one to five points, according to their opinion and perception of the last month.…”
Section: Methodsmentioning
confidence: 99%
“…There is interest in assessing the perception of sick and healthy populations' physical, mental, and social well-being, especially pregnant women [3][4][5][6][7][8]. The anatomical, physiological, and biochemical changes accompanying pregnancy, emotional maturation, and women's interaction with their environment contribute to the perception of well-being and quality of life [3,4,[7][8][9][10]. Quality of life assessment in pregnant women has preventive reasons since physical, psychological, and environmental health deterioration has negative obstetric and perinatal impacts such as preterm delivery and low birth weight [5].…”
Section: Introductionmentioning
confidence: 99%